CONCEPTUAL METAPHOR IN RUSSIAN: COLOR AND EMOTION DOMAINS - Qadamboyeva Muhayyo Ravshanbek qizi, (TADQIQOTLAR, 2026)
Abstract   This article examines the intersection of color and emotion in Russian conceptual metaphor, drawing on lexical data from  Metaphors in Russian — Animals, Colors, Emotions, Sports (Bobrova, Kisselev & Lantolf, 2018). Using Conceptual Metaphor Theory (Lakoff & Johnson, 1980) as its analytical framework, the study investigates how color terms in Russian encode abstract cultural values and how the four emotions catalogued in the dictionary — anger, happiness, love, and sadness — recruit multiple structurally distinct source domains. A central finding is that the two domains are not independent: red, white, black, and green each appear within emotion metaphors as markers  of  observable  physiological  states,  creating  a  cross-domain  color-emotion interface  grounded  in  the  visible  bodily  correlates  of  arousal.  At  the  same  time, culturally  specific  elaborations  —  particularly  the  density  of  black-color  illegality metaphors and the Orthodox-inflected anger expressions — demonstrate that embodied universals  are  always  shaped  by  historical  and  cultural  experience.  The  article concludes with brief reflections on the implications for advanced Russian language pedagogy.